The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.jse.2018.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of arthroscopy in the treatment of anterior glenoid rim fractures: a comparison with open surgery

Abstract: OATAO is an open access repository that collects the work of some Toulouse researchers and makes it freely available over the web where possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 24 publications
2
20
0
1
Order By: Relevance
“…3,5,9 Arthroscopic fixation with screws has been described by Cameron 5 through a case report, and several authors have reported their results using the arthroscopic fixation technique 10,11 or ORIF using screws. 3,9 Only one study 12 has compared arthroscopic fixation and ORIF using screws, reporting similar functional scores. The functional results and complication rates of similar previous studies and the current study are summarized in online Appendix.…”
Section: Discussionmentioning
confidence: 99%
“…3,5,9 Arthroscopic fixation with screws has been described by Cameron 5 through a case report, and several authors have reported their results using the arthroscopic fixation technique 10,11 or ORIF using screws. 3,9 Only one study 12 has compared arthroscopic fixation and ORIF using screws, reporting similar functional scores. The functional results and complication rates of similar previous studies and the current study are summarized in online Appendix.…”
Section: Discussionmentioning
confidence: 99%
“…However, open surgery including arthrotomy with splitting or detachment of the subscapularis tendon is associated with several potential complications due to the substantial soft-tissue injury or owing to the risk of fracture fragmentation. Range of motion is poorer and the complication and reoperation rates are higher after open surgery compared with arthroscopic techniques 3, 4. Arthroscopy enables perfect visualization of the articular surface, minimizes the need for soft-tissue dissection, and offers the opportunity to both detect and address concomitant intra-articular injuries.…”
Section: Discussionmentioning
confidence: 99%
“…However, surgical treatment of intra-articular glenoid fractures remains technically challenging. Traditionally, these procedures have been performed through an extensive open approach with internal screw fixation, which is associated with numerous potential intraoperative and postoperative complications 3, 4. As a result, several arthroscopic techniques have been developed to minimize the morbidity of open surgery.…”
mentioning
confidence: 99%
“…Various open techniques have been described for treating displaced articular glenoid fractures that require this kind of approach, with both intraoperative and postoperative risks. 8,9 Several arthroscopic techniques also have been described for reducing and fixing fractures with screws through anterior portals, crossing the subscapularis and involving the corresponding neurovascular risks. 10,11 Others include the use of instability anchors placed in the main glenoid fragment, crossing the displaced fragment with the sutures, so that when knotting is performed, the fracture is reduced and stabilized.…”
mentioning
confidence: 99%